2021
DOI: 10.18553/jmcp.2021.27.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of oral semaglutide added to current antihyperglycemic treatment for type 2 diabetes

Abstract: BACKGROUND:Oral semaglutide is the first oral formulation of a glucagon-like peptide 1 (GLP-1) receptor agonist to be approved in the United States for glycemic control in people with type 2 diabetes mellitus (T2DM).While oral semaglutide is not indicated for reduction of cardiovascular event risk, its label does include evidence of no increase in cardiovascular risk in people who received oral semaglutide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Rose et al also noted a significant increase in the monthly cost of hypoglycemic agents after initiating GLP-1 analogues ( Rose et al, 2020 ). Our study found that Semaglutide had higher cost and comparable outcomes with regard to HbA1C reductions compared to other diabetes treatments, a finding that contrasts with some studies while aligning with others ( Ramos et al, 2020 , Ehlers et al, 2022 , Guzauskas et al, 2021 , Gorgojo-Martínez et al, 2020 , Bain et al, 2020 , Hunt et al, 2019 , Capehorn et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Rose et al also noted a significant increase in the monthly cost of hypoglycemic agents after initiating GLP-1 analogues ( Rose et al, 2020 ). Our study found that Semaglutide had higher cost and comparable outcomes with regard to HbA1C reductions compared to other diabetes treatments, a finding that contrasts with some studies while aligning with others ( Ramos et al, 2020 , Ehlers et al, 2022 , Guzauskas et al, 2021 , Gorgojo-Martínez et al, 2020 , Bain et al, 2020 , Hunt et al, 2019 , Capehorn et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Studies in multiple countries have also variously found oral or s.c. formulations of semaglutide to be cost-effective compared with medications such as insulin, empagliflozin, liraglutide, and dulaglutide for the treatment of T2D [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 or reduction in health event probabilities (e.g., myocardial infarction [MI], stroke). 31 , 32 Prior work has demonstrated that the health effects of GLP1RA or SGLT2I are not fully captured by reductions in risk factors. 33 , 34 Thus, we chose to model the direct reduction in health event probabilities for the base-case analysis, to allow for a maximum estimate of drug benefit.…”
Section: Methodsmentioning
confidence: 99%